Communication In The Meratus Geopark Community For Job Diversification and Innovation In Rural Areas - Bachruddin Ali Akhmad; Muhammad Ainani; Sarwani (Jogjakarta Communication Conference (JCC), 2024)
This study aims to determine and describe how communication in the Meratus Geopark community in carrying out job diversification as an effort to improve the economy. The research was conducted in Belangian Village, Aranio Subdistrict, Banjar Regency, South Kalimantan Province, which is included in the Meratus Geopark area which has been designated by the Indonesian National Geopark Committee (KNGI) as an Indonesian National Geopark in 2018 and the first Geopark in Kalimantan. This research uses data collection techniques of documentation, observation, and in-depth interviews. Qualitative data from key informants, farmers and gardeners will be elaborated in FGD activities. The collected data is then processed using qualitative data analysis techniques from Miles and Huberman. Based on the results of the research, it was found that communication in the community in Belangian village has a very important opinion leader role in job diversification. The role of opinion leader is the role of leader, innovator, motivator, visual information center, and role model. With this role, opinion leaders have succeeded in providing innovations in rural employment diversification that can increase community income.